Essays in Empirical Asset Pricing - Aleksandra Anna Rzeznik (Copenhagen Business School (CBS), 2017)
This thesis consists of three essays investigating financial and real estate markets and identifying a relationship between them. A 2008 financial crises provides a perfect example of sizeable interactions between US housing market and equity prices, where a negative shock to house prices triggered a word-wide recession. Therefore, understanding forces driving investors behaviour and preferences, which in turn affect asset prices in both equity and housing market are of great interest.
hdl:10398/9436
Keywords: 650